Caption pada Foto Berita di Suratkabar Harian Ibukota Berperan Memberikan Gambaran Mengenai Isinya: Studi kasus: Suratkabar harian Republika - Amalia Rizky Fatonah; Cecep Gunawan; Susilawati Tabrani (Jurnalistik dan Media, 2023)
Photo journalism is Photo news should capable displays situation covers completeness a news so that function _ Photo in journalism is for interesting attention reader. So, that writing which own Photo in it will more interesting than information or news which only own text that writing a lot. So readers with easy get description regarding fill photos presented _ so required information (caption) regarding fill Photo that. Gani (2013: 152) explains that Captions are information from A Photo For give explanation in a way short but details about fill photo. How Presentation Caption on Photo News in Newspapers daily Capital role give description about its contents. (Study case: Newspaper daily Republica). With formula problem the study focus about presentation caption on Photo news. Method research used is method qualitative with approach analysis fill. From studies literature obtained criteria analysis includes, 1. Text at least two photos sentence, 2. Text Photo is one unity from photo, 3. Sentences first explain ganbar, next explain regarding the data held, 4. Text Photo must contain elements 5 W and 1 H., 5. Text Photo made with sentence active and simple. Results analysis there is one edition in matter elements 5W and 1H only reflect element what and where.